Paraneoplastic Neurological Syndromes and Beyond Emerging With the Introduction of Immune Checkpoint Inhibitor Cancer Immunotherapy - Valencia-Sanchez, Cristina; Zekeridou, Anastasia (Frontiers in Neurology, 2021)
Paraneoplastic neurological syndromes are more commonly seen with malignancies such as small cell lung cancer, thymoma, gynecological malignancies and breast cancer as well as seminoma. With the introduction of immune check point inhibitor (ICI) cancer immunotherapy we see an increase of autoimmune neurological complications in patients with malignancies not traditionally associated with paraneoplastic neurological syndromes, such as melanoma and renal cell carcinoma. Immune checkpoint inhibitors enhance antitumor immune responses resulting often in immune-related adverse effects that can affect any organ, including the central and peripheral nervous system, neuromuscular junction and muscle. Neurological complications are rare; neuromuscular complications are more common than central nervous system ones but multifocal neurological presentations are often encountered. The vast majority of neurological complications appear within 3 months of ICI initiation, but have been described even after ICI cessation. Neural autoantibody testing reveals autoantibodies in approximately half of the patients with CNS complications. Early suspicion and diagnosis is critical to avoid worsening and improve outcomes. Therapeutic strategies depend on the severity of the symptoms and initially typically involve discontinuation of ICI and high dose steroids. Further immunosuppression might be necessary. Outcomes are dependent on patient’s characteristics and clinical presentations.